Use of social media by academic librarians in Iraq - Saleem, M.; Aly, Anne; Genoni, Paul (2015)
Purpose – The purpose of this study is to identify the nature and extent of the “information gap” in Iraq and explore perspectives on international academic library collaboration using social media that may assist in reducing this gap. The study investigates the information gap in Iraq in the context of the country's recent history of political and social upheaval. Design/methodology/approach – The study uses qualitative data collected through interviews with academic library managers, librarians and researchers in both Australia and Iraq. Findings – The findings demonstrate that currently academic librarians in Iraq and Australia use social media differently. The degradation of critical research infrastructure and reliable communication means that Iraqi librarians rely heavily on informal communication channels. The study finds that use of social media offers will enhance collaboration by Iraqi academic librarians and reduce the information gap. Research limitations/implications – There are some limitations in terms of selection sampling, approaching Iraqi participants and average quality of connections. It is suggested that snowballing and chain sampling should be used. Social implications – The ethical challenges that are faced by the Iraqi community with social cultural systems are in the early stages of valuing higher education and a scholarly communication system based on unfamiliar models. Originality/value – This study represents the first attempt to assess the information gap that exists in the wake of recent political and social upheaval, and to explore ways in which Iraqi librarians use social media to redress this gap.